Die Glossolalie der Liebe Geschlechterverhaeltnisse und Liebesdiskurse in den Texten Valerija Narbikovas - Lange, Katrin (Slavistische Beitraege, 2001)
Love discourses, according to the basic thesis of the work, are figurative in Narbikova's texts as constituting the text. Their characteristic is the shift from (love) semantics to a specific (love) rhetoric. Love discourses in the textual presentation are no longer constituted through the traditional narration of love stories or stories about love, but through a practice of love-speech. As a result, language no longer functions as a means of description, but itself becomes the object of description and reflection. Examining this phenomenon in conjunction with the theme of love discourses is the main interest of the work.